Apomorphine in idiopathic restless legs syndrome: an exploratory study. Issue 2 (14th January 2005) - Tribl, G G; Sycha, T; Kotzailias, N; Zeitlhofer, J; Auff, E
Abstract : Background: Dopaminergic and opioidergic drugs have been found to be effective in patients with restless legs syndrome (RLS). Objectives: To test the effect of apomorphine—a combined opioidergic and dopaminergic agonist—and subsequent selective antagonism by naloxone and metoclopramide on subjective and objective symptoms in patients with idiopathic RLS. Methods: Nine patients with RLS were pretreated with oral domperidone for three days. A modified suggested immobilisation test (SIT) was carried out between 8 pm and 1 am under the following conditions of intravenous drug administration: baseline–apomorphine–apomorphine plus naloxone–apomorphine plus metoclopramide. Outcome variables were a visual analogue scale (VAS) of subjective RLS symptoms and EMG documented periodic leg movements while awake (PLMW). Results: Compared with baseline, apomorphine resulted in a rapid and significant improvement in subjective RLS symptoms as measured by VAS (54.5% improvement; p = 0.011), and an almost immediate cessation of PLMW, measured by PLMW index (98.0% improvement; p = 0.012). Neither additional naloxone nor metoclopramide blocked this effect significantly. While given apomorphine with metoclopramide, there was a trend to reappearance of PLMW. Conclusions: Apomorphine may be an effective treatment for idiopathic RLS. Its effectiveness may reflect both to its dopaminergic and its opioidergic activity, and is not diminished significantly by blocking only one of these pathways. The trend to a worsening of the PLMW index with metoclopramide hints at a primarily dopaminergic effect of apomorphine in idiopathic RLS.